The formatting of space and time in totalitarian historical discourse: On the example of soviet historiography - Chekanov, Vsevolod Iu. (Linguistics and Culture Review, 2021)
The subject of this article is the influence of socio-political engagement in non-democratic societies on the formation of scientific and historical discourse and on its further functioning and use for non-historical – political and educational purposes. It is analyzed not only from the point of view of the unique features inherent exclusively to totalitarianism, but rather as a derivative of socio-political requests for history that arise and are realized in any society, constantly becoming more complex over time. For Soviet totalitarianism, a characteristic feature of such requests was the absolutization of revolutions, which were interpreted as pivotal, milestone events that signified the main content of the progress of social development at literally all its stages. Because of this, Soviet historiography and the historiography of countries dependent on the USSR was characterized by attempts to “conceptually update the status” of a number of historical events, even those that preceded revolutions in their generally accepted meaning. In addition, an in-depth study of revolutions was characterized by the introduction of new terminology into scientific circulation and the identification of new elements of the division of historical time and space within revolutions.